A study on Affin Bank Berhad: the indicators toward bank performance after merged based on liquidity and leverage analysis / Norazlina Abdullah - Abdullah, Norazlina (Faculty of Business and Management, 2011)
This paper examined the indicators toward Affin Bank Berhad performance after merged based on liquidity and leverage analysis. The dependent variable (DV) used is the returns on equity represent bank performances and the independent variable (IDV)comprised of quick ratio represent liquidity analysis while debt ratio and debt to equity ratio represent leverage analysis. All of data collected from company’s financial statement for period ten years every quarterly. The data has analyzed using econometric view 7.0 to test whether the performance after merged influence in generate return based on liquidity and leverage analysis. The analysis showed that all of the stated variables (quick ratio, debt ratio, and debt to equity ratio) significant towards the returns on equity of the bank. It was found that there was a negative relationship between quick ratio and debt ratio on bank performances respectively while there was a positive relationship between debts to equity ratio on bank performances thus conclude that equity financing contribute in generate more return on Affin Bank Berhad